The agony of ethics and anthropology. Notes from Manuel Marzal's thought - Mujica Bermúdez, Luis (2008)
This paper is divided into three different sections. The first sectionconsiders the annotations of Manuel Marzal, an anthropologist and professor at the Pontificia Universidad Católica del Perú who passed away in the year 2005, about ethics as a concern coming form an anthropological perspective. Secondly, the article presents a balance on the bibliography about this issue, contrasting Marzal’s preoccupations with the latest bibliography, mainly Peruvian, which deals with ethics and morals in an explicit or implicit sort of way. Finally, living in the post-political violence and Commission for Truth and Reconciliation Final Report period, in order to make an anthropology on ethics one has to consider two methodological references and four dimensions to explore the people’s behaviors in relationto others. The methodological references require a «dense description » on morality to try to understand the simplicity of the relations and investigate and reflect on a multidisciplinary perspective. The four dimensions in which to explore ethics are daily life, religiosity, economics and politics.